â€œANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Konsumen KOPIKITA Semarang).â€ - Wulandari, Nur; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2013)
This study aims to determine how big the influence of product quality, service quality, andlocation to consumer satisfaction on KOPIKITA. The problem that facing by KOPIKITA isconsumerâ€™s satisfaction which decreasing, as seen from a lot of complain received from customer.And this research also aims to analyze the most dominant factors that influence on consumersatisfaction of KOPIKITA.Population of this research are consumers of KOPIKITA. Samples were taken of 100respondents by using non-probability sampling technique with purposive sampling approach. Datawas collected by using a survery method through quetionnaires which were filled out byconsumers. Then, the obtained data were analyzed using multiple regression analysis. Thisanalysis includes: validity test,reliability test, classic assumption test, multiple regression analysis,hypothesis testing through the t test and F test, and coefficient of determination analysis (RÂ²).From the analysis result, the indicators in this study are valid and reliables. The mostdominant factor that influence on consumer satisfaction is product quality follow the servicequality, and the last is location. Then though the F Test can be seen that the independent variablesfeasible to test the dependent variable. The result of Adjusted R Square is 55%, it means thatindependent variable can explain about 45% of dependent variable.